Drug-Induced Anaphylaxis in Latin American Countries (2015)
ABSTRACT: Background: Information regarding the clinical features and management of drug-induced anaphylaxis (DIA) in Latin America is lacking. Objective: The objective of this study was to assess implicated medications, demographics, and treatments received for DIA in Latin American patients referred to national specialty centers for evaluation. Method: A database previously used to compile information on drug-induced allergic reactions in 11 Latin American countries was used to identify and characterize patients presenting specifically with a clinical diagnosis of DIA. Information regarding clinical presentation, causative agent(s), diagnostic studies performed, treatment, and contributing factors associated with increased reaction severity was analyzed. Results: There were 1005 patients evaluated for possible drug hypersensitivity reactions during the study interval, and 264 (26.3%) met criteria for DIA. DIA was more frequent in adults and in elderly females (N = 129 [76.6%] and N = 30 [75%], respectively) compared with children and/or adolescents (N = 21 [42.9%], P < .01). Severe DIA was less frequent with underlying asthma (N = 22 vs 35 [38.6% vs 61.4%], P < .05) or atopy (N = 62 vs 71 [43% vs 59% ], P < .01). Nonsteroidal anti-inflammatory drugs (NSAIDs) (N = 178 [57.8%]), beta-lactam antibiotics (N = 44 [14.3%]), and other antibiotics (N = 16 [5.2%]) were the most frequently implicated drug classes. Anaphylaxis was rated as severe in N = 133 (50.4%) and anaphylactic shock (AS) was present in N = 90 (34.1%). Epinephrine was only used in N = 73 (27.6%) overall, but in N = 70 (77.8%) of patients with AS. Conclusion: In Latin American patients referred for evaluation of DIA, NSAIDs and antibiotics were implicated in approximately 80% of cases. Most of these reactions were treated in the emergency department. Epinephrine was administered in only 27.6% of all cases, although more frequently for anaphylactic shock. Dissemination of anaphylaxis guidelines among emergency department physicians should be encouraged to improve management of DIA.